Metode, Model, Strategi, Serta Desain Kurikulum dan Rencana Pembelajaran Pendidikan Agama Kristen dalam Keluarga. (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to examine the methods, models, strategies, as well as the design and development of the Christian Religious Education curriculum within the family. The research employs a qualitative approach with a descriptive type through library research, using data sources such as books, scientific journals, and relevant articles. The results of this study indicate that faith education in the family should be carried out holistically through various methods such as modeling, habituation, teaching, and mentoring. In addition, educational models such as the theocentric, relational, and participatory models provide clear direction in nurturing children’s faith. Effective strategies include modeling, dialogical communication, spiritual habituation, mentoring, and discipline based on love. Meanwhile, a simple family-based curriculum that includes objectives, materials, methods, media, and evaluation is essential to support a well-directed educational process. The success of Christian Religious Education in the family largely depends on the active role and consistency of parents in implementing methods, models, strategies, and curriculum in an integrated manner. With the right approach, the family can become an effective center of faith education in shaping children who are faithful, have strong character, and are prepared to face life’s challenges.